Women's Empowerment: Evidence from the Corn-Tortilla Value Chain in the Central Valley’s Region and the Isthmus of Tehuantepec, Oaxaca, Mexico. (2023)
This article explores the level of Women’s Empowerment (W’E) from six empowerment domains: decision-making, autonomy, access and control of resources, community participation, and participation in business management, within the context of the corn-tortilla value chain. A semi-structured questionnaire was used to collect data through the survey method and participant observation. The sample consisted of 136 women producers from two municipalities, 67 from Santa María Xadani in the Isthmus of Tehuantepec and 69 from San Antonio de la Cal in the Central Valleys of Oaxaca, Mexico. The results highlight that women exercise five of the six explored domains of empowerment, two with high levels and three with medium levels of empowerment. The women’s income from selling their corn tortillas is used to buy food, raw materials, and health services. Much of their time is spent on corn tortilla production and marketing, and household activities. Finally, this study makes implications for public policy to contribute with the generation of strategies that raise the levels of W’E in agrifood systems in rural contexts.  JEL Codes: I31, J16, P42, Q01, R11 Received: 13/01/2023.  Accepted: 24/05/2023.  Published: 26/06/2023.